Repercussions of International Trade on the Market Power of Firms in Different Market - RASHID, Muhammad Mustafa (Journal of Advanced Research in Management; Vol 10 No 1 (2019): JARM Volume X Issue 1(19) Summer 2019, 2019)
The purpose of this paper is to provide an introduction of market power in different market structures and how this market power diminishes because of international trade and the effects on welfare. A review of relevant literature from Pugel (2012), McConnel Bruce and Flynn (2012) and Bernheim and Winston (2014) provides the effects of international trade on the market power conditions in different market structures and the effects on welfare. Asprilla, Berman, Cadot and Jaud (2019), Feenstra (2018), Devereux and Lee (2001) and Krugman (1994) serve to provide further evidence through PTM literature, gains from trade, bilateral exchange rate shocks and protectionism.